2006
DOI: 10.1016/j.jvs.2006.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Chronic venous leg ulcers benefit from surgery: Long-term results from 173 legs

Abstract: On the basis of the results from the 7 years of data from functional surgery of venous leg ulcers and as a result of the outcomes of our study, we recommend surgical treatment of venous leg ulcers at any stage. We therefore conclude that surgery is indicated before an ulcer is intractable to treatment. In general, our findings are based on the understanding and identification of the causes and symptoms of venous ulceration and illustrate that standard surgical methods can be applied for the therapy of venous l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 29 publications
2
55
0
2
Order By: Relevance
“…7 Abolition of superficial refluxes has been shown to achieve beneficial effects on ulcer healing even in the presence of concomitant deep venous refluxes and can be offered on a general basis. 8,9 In this study, we sought to identify the exact reflux routes associated with medially or laterally located venous leg ulcers. To achieve this aim, we prospectively investigated 183 legs with active leg ulcers presenting with venous reflux, using extended duplex ultrasound examination focusing on the ultimately dominant venous reflux routes in addition to classical venous mapping.…”
mentioning
confidence: 99%
“…7 Abolition of superficial refluxes has been shown to achieve beneficial effects on ulcer healing even in the presence of concomitant deep venous refluxes and can be offered on a general basis. 8,9 In this study, we sought to identify the exact reflux routes associated with medially or laterally located venous leg ulcers. To achieve this aim, we prospectively investigated 183 legs with active leg ulcers presenting with venous reflux, using extended duplex ultrasound examination focusing on the ultimately dominant venous reflux routes in addition to classical venous mapping.…”
mentioning
confidence: 99%
“…Even if their clinical meaning is still under debate [17][18][19], their closure in patients presenting with severe venous insufficiency, such as class C5 and C6 according to the CEAP classification, significantly contributes to better results of treatment [20][21][22][23][24][25][26][27][28]. Incompetence of perforating veins can be of primary or secondary nature.…”
Section: Discussionmentioning
confidence: 99%
“…Even though endovenous laser treatment is an advance in the minimized surgical approach, it can never fully displace accepted surgical procedures. [15] Anatomical failures are to be recognized in endovenous ablations procedures and should be combined with open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown one year recurrence of 25% and 3 year recurrence of 38%. [14] [15] Previous studies have failed to show a benefit from superficial venous surgery in terms of haemodynamic change or ulcer healing in patients with mixed deep and superficial reflux. [16] They had included primary varicose ulcer procedures and ulcers associated with deep venous insufficiency and postthrombotic legs.…”
Section: Anatomic Failure Has Been Classified As Followsmentioning
confidence: 99%